Didactical Design Development of Two Variables Linear Equation - Hani Nurhasanah; Sufyani Prabawanto; Encum Sumiaty ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
The learning process students must be trained to understand concepts well, not only memorize the material. Learning will be effective if students understand the mathematical concepts being studied. It was found learning difficulties especially in learning linear equations caused by a lack of understanding of the concepts and the way the teacher taught. The most common difficulties were in presenting mathematical concepts, understanding information about questions, and interpreting data in the design requested. Based on the problem, Author developed didactical design of two-variable linear equations material that aims to minimize the difficulties that occur. The research method used qualitative method that was Didactical Design Research (DDR). The subjects of the study were Bandung junior high school students, class VIII even semester who got the material of two-variable linear equations using Curriculum 2013. In general, didactical design implemented need to be maintained. Didactical design developed can minimize the obstacles of student learning difficulties. However, the researcher recommends the existence of a research on the development of didactical design of the concept of two-variable linear equations with various improvements, both in terms of deeper concepts, presentation, and predictions of student responses.